Implementation of Marketing Strategy: A Case Study of an Online Upcycling Fashion Brand in Indonesia - Anindita Hanadhyas; Nuri Wulandari (Bina Nusantara University, 2022)
The continuous growth of the fashion industry leaves tons of discarded clothing and garments. One way to address this issue is by upcycling or assembling worn or leftover garments into a new piece of clothing. With the growing sustainable awareness in Indonesia, consumers have started to look for clothing brands applying a sustainable practice. The research investigated the external and internal factors that could affect sales as well as brand awareness and identified the marketing strategy of a new upcycling clothing brand in Indonesia, Kawan. The research was conducted by understanding the external and internal factors using qualitative and quantitative methods. The internal data were from interviews with the owner of Kawan, customers and potential customers of Kawan. They were analyzed by the Valuable, Rare, Imperfectly Imitable, Organization (VRIO) and Marketing Mix (Product, Price, Place, and Promotion (4P)) framework. Meanwhile, the external factors were examined by the Political, Economic, Sociocultural, Technology, Ecological, Legal (PESTEL) framework and benchmarking. The data for PESTEL analysis were derived from news, reports, and an interview with the owner of Kawan. A survey was also conducted to women in Indonesia to formulate the marketing strategy using Marketing Mix framework. The results show the product characteristics for upcycling clothing brand and essential types of information for the promotion. They are essential in value creation and delivery for upcycling fashion brands. It is expected to contribute to the sales issue that Kawan has experienced and generate the marketing strategy for the issue.